2012
DOI: 10.1016/j.jcma.2012.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of the external auditory canal

Abstract: Primary cancers of the external auditory canal (EAC) are rare and most are squamous cell carcinomas. We report the case of a 78-year-old man who visited our institution with a 5-month history of right-side intermittent otalgia and ear fullness. Otoscopic examination showed a bulging mass arising from the superior and posterior aspects of the right EAC, and incision biopsy confirmed the lesion as adenoid cystic carcinoma (ACC). Lateral temporal bone resection in conjunction with total parotidectomy and neck dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 24 publications
1
32
1
Order By: Relevance
“…Previous reports have indicated that ACC of the external auditory canal is a tumor of adulthood, with a definite peak incidence in the fourth and fifth decades of life, occurring rarely in children and adolescents . In our study, the median age at diagnosis was 49 years.…”
Section: Discussionmentioning
confidence: 53%
“…Previous reports have indicated that ACC of the external auditory canal is a tumor of adulthood, with a definite peak incidence in the fourth and fifth decades of life, occurring rarely in children and adolescents . In our study, the median age at diagnosis was 49 years.…”
Section: Discussionmentioning
confidence: 53%
“…The mean age for ACC is the fifth decade and it is two times more common in women than men. The most common clinical symptoms are otorrhea, pain, hearing loss, bleeding and a mass in the ear canal [5]. A wide deep biopsy should be performed in every EAC mass, as it is essential for the establishment of the diagnosis of adenocystic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Serious diagnostic difficulties may be encountered because of varied clinical and histological manifestations. SCAP presenting as a soft tissue mass that persist in the EAC should be differentiated from other benign neoplasms, such as cylindroma, papilloma, malignant ceruminous gland tumors, such as squamous cell and basal cell carcinomas, and even tuberculosis [12]. Furthermore, in cases of masses that totally obstruct the canal, only radiological investigations may reveal the exact extent of the mass.…”
Section: Discussionmentioning
confidence: 99%